2016
DOI: 10.1590/1678-457x.05315
|View full text |Cite
|
Sign up to set email alerts
|

Sensory perception of the fermented goat milk: potential application of the DSC method

Abstract: Goat milk and its derivatives present proven beneficial health properties; however, some sensory aspects associated to consumers' expectations restrict the consumption growth for these products. In this work, fermented caprine milk formulations have been evaluated utilizing the methodology of Discourse of the Collective Subject (Discurso do Sujeito Coletivo -DSC) associated to sensory analysis, in order to evaluate the perception of fermented caprine milk by consumers. The physicochemical and microbiological r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
2
0
1
Order By: Relevance
“…The milk fatty acid profile has been changed when feeding goats with ELS and there were minor changes in PSC compared to Control (Table 4). The ELS and PSC diets did not influence the proportions of C6:0, C8:0 and C10:0, fatty acids responsible for the particular sensory properties of goats´ milk (Bessa et al, 2016) and health benefits providing better digestibility of goat milk (Zenebe et al, 2014). Bernard et al (2015) found that SCFA, specifically C6:0, C8:0 and C10:0, were lowered in milk when feeding goats with 216 g/kg DM of extruded linseed in goats´ diets Contains C18:1 t7 + t8 as a minor components, 2 Contains C18:1 t10 as a minor component, 3 Contains C18:1 t12 + t13 + t14 as a minor components, 4 Contains C18:1 c14 as a minor component, 5 Contains C19:0 a minor component, 6 Contains C18:2 t9 t12 + t8 c12 + c9 t13 a minor components; SEM-standard error of mean; a,b Row means with different superscripts differ significantly at P < 0.05 Proportions of stearic (C18:0), OA, vaccenic (VA, C18:1 t11) acid and CLA remained unaffected by dietary treatments.…”
Section: Resultsmentioning
confidence: 99%
“…The milk fatty acid profile has been changed when feeding goats with ELS and there were minor changes in PSC compared to Control (Table 4). The ELS and PSC diets did not influence the proportions of C6:0, C8:0 and C10:0, fatty acids responsible for the particular sensory properties of goats´ milk (Bessa et al, 2016) and health benefits providing better digestibility of goat milk (Zenebe et al, 2014). Bernard et al (2015) found that SCFA, specifically C6:0, C8:0 and C10:0, were lowered in milk when feeding goats with 216 g/kg DM of extruded linseed in goats´ diets Contains C18:1 t7 + t8 as a minor components, 2 Contains C18:1 t10 as a minor component, 3 Contains C18:1 t12 + t13 + t14 as a minor components, 4 Contains C18:1 c14 as a minor component, 5 Contains C19:0 a minor component, 6 Contains C18:2 t9 t12 + t8 c12 + c9 t13 a minor components; SEM-standard error of mean; a,b Row means with different superscripts differ significantly at P < 0.05 Proportions of stearic (C18:0), OA, vaccenic (VA, C18:1 t11) acid and CLA remained unaffected by dietary treatments.…”
Section: Resultsmentioning
confidence: 99%
“…However, the influences of non-sensory and sensory factors on consumers' perceptions of functional foods have been little studied. As a functional food, most of the previous studies on milk have focussed on, for example, assessing the microbiological quality of milk (Islam et al, 2018), evaluating fermented caprine milk's perceptions (Bessa et al, 2016), the effects of TV commercials on customers' buying behaviour (Khuong and Nguyen, 2015), production sustainability (Asselt et al, 2015), demand and market opportunities (Kuma et al, 2012;Cheng et al, 2014), demand and supply (Chavas and Klemme, 1986;Popescu, 2015), comparing flavour and texture (Oupadissakoon et al, 2009), consumption frequency and patterns (Grebitus et al, 2007), and consumers' perceptions and attitudes towards milk (Perkins and Deeth, 2001). Little literature has measured the consumers' perceptions of attributes like labelling information (extrinsic cue) and sensory (intrinsic cues) on purchase intentions for milk.…”
Section: Introductionmentioning
confidence: 99%
“…Kebiasaan makan dan standar budaya mempengaruhi secara langsung daya terima konsumen terhadap makanan. 18 Susu kedelai memiliki daya terima yang rendah oleh konsumen. Hal ini disebabkan karena rasa langu dari susu kedelai.…”
Section: Pembahasanunclassified